Strategies to expand corporate autonomy by the tobacco, alcohol and sugar-sweetened beverage industry: a scoping review of reviews - Hoe, Connie; Weiger, Caitlin; Minosa, Marela Kay R.; Alonso, Fernanda; Koon, Adam D.; Cohen, Joanna E. (Globalization and health, 2022)
Noncommunicable diseases contribute to over 70% of global deaths each year. Efforts to address this epidemic are complicated by the presence of powerful corporate actors. Despite this, few attempts have been made to synthesize existing evidence of the strategies used to advance corporate interests across industries. Given this, our study seeks to answer the questions: 1) Is there an emergent taxonomy of strategies used by the tobacco, alcohol and sugar-sweetened beverage (SSB) industries to expand corporate autonomy? 2) How are these strategies similar and how are they different?